Control and Inventory of Raw Materials in Bread Companies To Minimize Raw Material Inventory - Syifani, Sheni Nahla; Handayani, Wiwik (Dinasti International Journal of Education Management and Social Science, 2025)
The high demand fluctuations caused SA Bakery to experience several problems such as lack of control over raw material inventory and excess shortages in raw material inventory. To help the company, this research aims to reduce inventory costs, reduce order frequency, and stabilize raw material inventory. In achieving these objectives, an operational management approach is applied in this study. One of the techniques in inventory control, namely, Material Requirement Planning (MRP) will be used. In implementing a good MPR system, the MRP Easy method integrates the inventory in the SA Bakery Bakery. In running the MRP Easy method by integrating information using software, one of the software is MRPEasy in the form of a dashboard and also an inventory management system to control the inventory system in it. The input used is BOM data, Orders, forecasting, MPS, and Inventory. The output obtained is in the form of purchase orders in the company every month in a period of 1 year, material plans, work orders and reports for the company. The results of the study found that the application of the control system in MRP provided forecasting results showing significant fluctuations in several months, such as June and September, which caused the potential for overproduction. In the context of MRP theory, this indicates the need for adjustments to safety stock and lead time so that the system can work optimally. MRP not only plays a role in purchasing planning, but also in managing production and distribution times, which in the case of SA Bakery is shown through the output of PO Quantity and capacity requirements analysis (CRP).